Hadith #1749 - Sahih Muslim - Ibn Ishaq محمد بن إسحاق بن يسار‎ (Sahih Muslim)
I heard al-Bara’ as saying that a man recited al-Kahf when an animal was there in the house and it began to take fright. And as he looked around, he found a cloud overshadowing it. He mentioned that to the Messenger of Allah (ﷺ). Upon this he said: O so and so, recite on (the surah) as- Sakina descends at the (recitation of the Qur’an) or on account (of the recitation) of the Qur’an.
Grade: Sahih

Hadith #2915 - Sahih Muslim - Ibn Ishaq محمد بن إسحاق بن يسار‎ (Sahih Muslim)
I asked Zaid b. Arqam: In how many military expeditions have you participated with Allah’s Messenger (ﷺ)? He said: In seventeen (expeditions). He (Abu Ishaq) said: Zaid b. Arqam reported to me that Allah’s Messenger (ﷺ) had led nineteen expeditions. And he performed Hajj only once after Migration, and that was the Farewell Pilgrimage. Abu Ishaq also said: The second (Hajj) he performed at Mecca (before his Migration to Medina)
Grade: Sahih